Emerging Evidence for Intrathecal Management of Neuropathic Pain Following Spinal Cord Injury - Karri, Jay; Doan, James; Vangeison, Christian; Catalanotto, Marissa; Nagpal, Ameet S.; Li, Sheng (Frontiers in Pain Research, 2022)
A high prevalence of patients with spinal cord injury (SCI) suffers from chronic neuropathic pain. Unfortunately, the precise pathophysiological mechanisms underlying this phenomenon have yet to be clearly elucidated and targeted treatments are largely lacking. As an unfortunate consequence, neuropathic pain in the SCI population is refractory to standard of care treatments and represents a significant contributor to morbidity and suffering. In recent years, advances from SCI-specific animal studies and translational models have furthered our understanding of neuronal excitability, glial dysregulation, and chronic inflammation processes that facilitate neuropathic pain. These developments have served advantageously to facilitate exploration into the use of neuromodulation as a treatment modality. The use of intrathecal drug delivery (IDD), with novel pharmacotherapies, to treat chronic neuropathic pain has gained particular attention in both pre-clinical and clinical contexts. In this evidence based narrative review, we provide a comprehensive exploration into the emerging evidence for the pathogenesis of neuropathic pain following SCI, the evidence basis for IDD as a therapeutic strategy, and novel pharmacologics across impactful animal and clinical studies.